WEATHERING DAMAGE EVALUATION OF ROCK PROPERTIES IN THE BUNHWANGSA TEMPLE STONE PAGODA, GYEONGJU, REPUBLIC OF KOREA - Lee Ch.H.; Yi J.E. (My University, 2007)
The stone pagoda of the Bunhwangsa temple in Republic of Korea was made of piling small brick-shaped stones. The majority of stone bricks are andesitic rocks with variable geneses. Rock properties of the pagoda roof suffer partial significant deterioration, such as multiple peel-offs, exfoliation, onion-peel-like decomposition, cracks forming round lines and falling-off stone pieces. The stylobates and tabernacles at the four corners are composed of granitic rocks, which are heavily contaminated by lichens and mosses. Some of these contamination marks show dark black or yellowish brown colors by inorganic secondary hydrates. The four tabernacles and northern face of the pagoda body have been exposed to relatively high humidity, which causes light gray efflorescence as stalactites between the northern and western sides of the body. The efflorescences are composed of calcite, gypsum and clay minerals. The stone lion statues at the southeast and northeast corners are made of alkali granite, while the others are lithic tuff. Total rock properties of the pagoda consist of 9,708 stone bricks. Among them, 11.0% are fractured, 6.7% are fallen off, and 7.0% show considerable surface efflorescence, which shows that the pagoda has been highly deteriorated by physical, chemical and biological weathering. The authors strongly suggest long-term monitoring and comprehensive conservation researches.
Keywords: STONE PAGODA; ANDESITE; GRANITE; LITHIC TUFF; CONTAMINATION; WEATHERING; KOREA